Pengaruh Motivasi, Disiplin Kerja dan Kompensasi Terhadap Kinerja Karyawan Pada CV Tiga Putra Jaya: The Effect of Motivation, Work Discipline, and Compensation on Employee Performance at CV Tiga Putra Jaya - Mediana Hasibuan; Faif Yusuf (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the influence of motivation, work discipline, and compensation on employee performance on CV Tiga Putra Jaya. In the competitive business world, employee performance is a key factor in determining the success of a company. Motivation, work discipline, and compensation are important variables that can affect individual productivity and performance in an organization. This study uses a quantitative method with a descriptive approach. Data was collected through a questionnaire distributed to 32 CV employees. Tiga Putra Jaya. Data analysis was carried out using multiple linear regression with the help of SPSS version 27 software. The results of the study show that motivation, work discipline, and compensation have a positive and significant effect on employee performance, both partially and simultaneously. Work discipline has the most dominant influence, followed by motivation and compensation. Based on the determination coefficient test, the variables of motivation, work discipline, and compensation simultaneously affected employee performance by 63%, while 37% were influenced by other factors outside this study. This research is expected to contribute to the development of human resource management strategies, especially in improving employee motivation and work discipline through a fair and transparent compensation program